Characterization and therapeutic potential of phage vB_Eco_ZCEC08 against multidrug-resistant uropathogenic Escherichia coli - Assmaa H. Hussein; Salsabil Makky; Raghda Hager; Ian F. Connerton; Ayman El-Shibiny (BMC Microbiology)
Abstract Background Urinary tract infections (UTIs) caused by antibiotic-resistant bacteria have become a significant public health concern. The increasing ineffectiveness of antibiotics has led to a renewed focus on investigating other strategies, such as bacteriophages, to target specific pathogenic bacteria and prevent future resistance. Results This study reports the isolation and characterization of bacteriophage vB_Eco_ZCEC08 targeting uropathogenic Escherichia coli (UPEC). Phage vB_Eco_ZCEC08 is morphologically a non-contractile tailed phage that exhibits strong lytic activity against UPEC with a short latent period of less than 15 min and a lysis time of 20 min to produce a high burst of around 900 phage particles per host cell. vB_Eco_ZCEC08 phage activity demonstrated exceptional stability against temperature [-80–60 ̊C], pH [2–11], UV exposure and incubation in artificial human urine. The phage effectively reduced UPEC counts over a range of infection rates, with MOI 1 the most effective, and which resulted in the limited emergence of phage-insensitive bacteria. A whole-genome study of the 47.926 bp vB_Eco_ZCEC08 phage identified one tRNA gene and 84 predicted genes. Comparative genomics and phylogenetic analysis suggest that the vB_Eco_ZCEC08 phage belongs to the same genus as the Salmonella phage vB_SenS_ST1 but represents a new species. Phage vB_Eco_ZCEC08 showed minimal cytotoxicity against human urinary bladder cancer and skin fibroblast cell lines. Conclusion vB_Eco_ZCEC08 phage demonstrates strong selective lytic activity against UPEC in the absence of any lysogenic behavior. These properties coupled with inherent physiochemical stability and low cytotoxicity support the development of vB_Eco_ZCEC08 as an alternative treatment for multidrug-resistant UPEC.